2020
DOI: 10.3390/nu12051245
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ionized Magnesium as a Measure of Supplement Bioavailability: Results from a Pilot Study for Randomized Clinical Trial

Abstract: Oral supplementation may improve the dietary intake of magnesium, which has been identified as a shortfall nutrient. We conducted a pilot study to evaluate appropriate methods for assessing responses to the ingestion of oral magnesium supplements, including ionized magnesium in whole blood (iMg2+) concentration, serum total magnesium concentration, and total urinary magnesium content. In a single-blinded crossover study, 17 healthy adults were randomly assigned to consume 300 mg of magnesium from MgCl2 (ReMag®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
(57 reference statements)
0
5
1
7
Order By: Relevance
“…Следующие два исследования [15,16] схожи тем, что для оценки биодоступности магния в качестве первичной конечной точки проводилась оценка концентрации ионизированного магния (iMg). В последнее время считается, что iМg может быть более физиологически релевантным маркером, чем общий магний (totalМg).…”
Section: Pharmacokinetic (Bioavailability) Studies Of Magnesium Prepa...unclassified
See 3 more Smart Citations
“…Следующие два исследования [15,16] схожи тем, что для оценки биодоступности магния в качестве первичной конечной точки проводилась оценка концентрации ионизированного магния (iMg). В последнее время считается, что iМg может быть более физиологически релевантным маркером, чем общий магний (totalМg).…”
Section: Pharmacokinetic (Bioavailability) Studies Of Magnesium Prepa...unclassified
“…Необходимо учитывать, что 20-30% от общего содержания магния в сыворотке связано с белками и считается физиологически неактивным, тогда как iМg составляет 60-70% от totalМg [17,18] и считается биологически активной формой магния в сыворотке крови [19]. Однако величина iMg нечасто используется в клинических исследованиях, вероятно, потому, что для этого требуется немедленный анализ iMg цельной крови и для измерения требуется специальное оборудование [15]. J. Zhan и соавт.…”
Section: Pharmacokinetic (Bioavailability) Studies Of Magnesium Prepa...unclassified
See 2 more Smart Citations
“…Despite the fact that magnesium deficiency is very frequent in the population and is associated with altered levels of other electrolytes and various diseases, its diagnosis still represents a challenge because, to date, there is no gold standard to measure its concentration. The study of Zhan and colleagues showed that to assess magnesium bioavailability, circulating ionised magnesium might be a more sensitive measure of acute oral intake of magnesium than serum and urinary magnesium [ 17 ]. Orlova and co-workers proposed a magnesium deficiency questionnaire based on questions grouped into five categories: wellbeing, lifestyle, pregnancy, disease and medication, as a non-invasive assessment tool that could help to diagnose magnesium deficiency [ 18 ].…”
mentioning
confidence: 99%